Pendekatan Eko-Pastoral dalam Penyembuhan Melalui Suara Alam - Sumakul, Yunita; Naleng, Delviana Tasya; Hontong, Merike; Ponto, Chanesa (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
The connection between humans and nature has a significant influence on various aspects of life, including physical, mental and spiritual health. The eco-pastoral approach is a combination of ecological principles and spirituality which aims to support a comprehensive healing process by utilizing natural elements, especially natural sounds. In the context of the environmental crisis and increasing mental health disorders, this approach offers a way to utilize nature as a means of healing that strengthens humans' relationship with God and the natural surroundings. Natural sounds, such as flowing water, birdsong, and the breeze, have therapeutic effects, helping to relieve stress, promote calm, and support spiritual healing. This article examines the eco-pastoral approach, the relationship between humans, nature and the healing process, as well as the role of natural sounds in therapy. This approach emphasizes the importance of balance between humans and nature as part of ecological and spiritual responsibility. Keywords : Eco-Pastoral Approach; Nature Therapy; Sounds of Natur e